Quality of life of cancer patients undergoing radiotherapy in the radiotherapy clinic at Hospital Universiti Sains Malaysia (HUSM) - Diana, Lapai (Universiti Sains Malaysia, 2009)
This cross sectional study assessed the QOL outcomes among cancer patients undergoing radiotherapy in Radiotherapy Clinic of HUSM. Study done to determined the domain of QOL of cancer patients which were physical, social/family, emotional and functional well-being based on FACT -G questionnaire. In addition, since the patients were from various demographic and clinical characteristics, this study also examined the association of these characteristics with their QOL outcomes. The questionnaire was given to the patients who were coming for their scheduled of radiotherapy. The sample was selected by systemic random sampling. The total sample size in this study was 52 (n=52). The statistical analysis shows that the most affected domain of QOL is physical well-being followed by functional wellbeing with the mean score and SO were 17.94(7.60) and 18.79(7.15) each. Social/family and emotional well-being was less affected of QOL domain with the mean score were 22.95(4.93) and 18.04(4.61) each. Besides that, apparently there is no association between age, sex, marital status, and stage of cancer to the QOL outcomes (p>0.05). Only educational level (p=0.02), employment (p=0.007) and household income (p=0.046) was found to have association to the QOL outcomes. Patients in a group of low educational level, unemployed and household income of <RM570.00 showed more moderate impairment of QOL. There is no patients experience severe impairment of QOL.